Accounting for Education and Career (ACE): Strengthening Senior High School Students’ Interest in and Readiness for Choosing an Accounting Major - Rinda Siaga Pangestuti; Mila A. Reyes; Supeni Anggraeni Mapuasari; Vita Elisa Fitriana; Reinhard Gritus Apriliano (SWARNA: Jurnal Pengabdian Kepada Masyarakat, 2026)
Abstract: Choosing a study program on the eve of graduation places senior high school students before a decision that is far from simple, while their picture of accounting and its employment prospects often remains hazy. This community service activity, themed Accounting for Education and Career (ACE), was held to strengthen students’ understanding, confidence, and interest with respect to the accounting major and profession. It took place on 20 July 2026 at SMA Negeri 2 Cikarang Barat with grade XII students as participants, combining a presentation on career prospects, educational games, and a question-and-answer session. The impact of the activity was measured through a 17-item self-perception questionnaire on a 1-5 Likert scale, completed by 60 students before and 59 students after the event, and then analyzed descriptively with an N-Gain computation. The participants’ average perception score moved from 3.81 to 4.00 on a scale of 5, equivalent to a shift from 76.1% to 79.9%, with an N-Gain of 0.16. The largest increase was recorded for interest in choosing the accounting major, from 3.23 to 3.68 (N-Gain 0.25), followed by confidence in settling on a course of study, from 3.53 to 3.86 (N-Gain 0.23). Both were the primary targets of the activity, whereas the three aspects outside those targets recorded the smallest increases. The magnitude of the N-Gain does fall in the low category, yet the direction of change clusters precisely on the targets that were aimed at. The presence of a practitioner speaker proved capable of strengthening students’ interest in and readiness for choosing an accounting major.